SOME SPECIFIC DETAILS OF THE SOUTHERN LITERARY TRADITION - Sobirjanova Oydina Rasuljon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotatsiya: "Southern literature " announces the conjunction of the US South and an expressive art — texts identified as belonging to a particular history, social organization, and cultural imaginary. This article describes and discusses Southern literature and the author’s .